A Practical and Fast Method To Predict the Thermodynamic Preference of ω‐Transaminase‐Based Transformations. Issue 17 (20th August 2015) - Meier, Robert J.; Gundersen, Maria T.; Woodley, John M.; Schürmann, Martin
Abstract A simple, easy‐to‐use, and fast approach method is proposed and validated that can predict whether a transaminase reaction is thermodynamically unfavourable. This allowed us to deselect, in the present case, at least 50% of the reactions because they were thermodynamically unfavourable as confirmed by experiment. Once a larger data base is established, in silico screening of several new reactions (new target molecules) can easily be performed each day.